2011
DOI: 10.1016/j.jmb.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of the S. cerevisiae Spt6 Core and C-Terminal Tandem SH2 Domain

Abstract: The conserved and essential eukaryotic protein Spt6 functions in transcription elongation, chromatin maintenance, and RNA processing. Spt6 has three characterized functions. It is a histone chaperone capable of reassembling nucleosomes, a central component of transcription elongation complexes, and is required for recruitment of RNA processing factors to elongating RNA polymerase II (RNAPII). Here, we report crystal structures of the 168 kDa Spt6 protein from Saccharomyces cerevisiae that together represent es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 65 publications
3
84
0
Order By: Relevance
“…Spt6 is a large protein (1451 amino acids in S. cerevisiae) with multiple domains that suggest interactions with DNA, RNA, and several proteins in addition to Spn1 (Doherty et al 1996;Johnson et al 2008;Dengl et al 2009;Close et al 2011). Among its domains are tandem SH2 domains at its carboxy-terminal end, the only SH2 domains in S. cerevisiae (Maclennan and Shaw 1993;Dengl et al 2009;Diebold et al 2010b;Sun et al 2010;Close et al 2011;Liu et al 2011).…”
Section: Spt6 and Fact: Factors Controlling Transcriptional Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Spt6 is a large protein (1451 amino acids in S. cerevisiae) with multiple domains that suggest interactions with DNA, RNA, and several proteins in addition to Spn1 (Doherty et al 1996;Johnson et al 2008;Dengl et al 2009;Close et al 2011). Among its domains are tandem SH2 domains at its carboxy-terminal end, the only SH2 domains in S. cerevisiae (Maclennan and Shaw 1993;Dengl et al 2009;Diebold et al 2010b;Sun et al 2010;Close et al 2011;Liu et al 2011).…”
Section: Spt6 and Fact: Factors Controlling Transcriptional Integritymentioning
confidence: 99%
“…Among its domains are tandem SH2 domains at its carboxy-terminal end, the only SH2 domains in S. cerevisiae (Maclennan and Shaw 1993;Dengl et al 2009;Diebold et al 2010b;Sun et al 2010;Close et al 2011;Liu et al 2011). The SH2 domains are required for Spt6 to interact with the CTD of Rpb1 of RNAPII, for normal levels of Spt6 recruitment to chromatin in vivo, and for wild-type function (Dengl et al 2009;Diebold et al 2010b;Mayer et al 2010;Sun et al 2010;Close et al 2011;Liu et al 2011).…”
Section: Spt6 and Fact: Factors Controlling Transcriptional Integritymentioning
confidence: 99%
“…7A). Since the tSH2 domain interacts with the phosphorylated CTD (24)(25)(26), deleting this domain should diminish CTD-dependent Spt6 recruitment. In agreement with a previous study (22), deleting the tSH2 greatly reduced Spt6 but not Pol II (Rpb3) occupancy in the ARG1, ADH1, and PMA1 coding regions ( Fig.…”
Section: Fig 4 Hdacs Promote Spt6 Recruitment To the Coding Regions mentioning
confidence: 99%
“…It possesses a tandem Src homology 2 domain (tSH2) that interacts with phosphorylated Pol II C-terminal domain (CTD) peptides in vitro and is required for full recruitment of Spt6 in vivo (22)(23)(24)(25)(26). Although these observations suggest that CTD phosphorylation is needed for Spt6 recruitment, the role of CTD phosphorylation in vivo in this process is not fully understood.…”
mentioning
confidence: 99%
“…Therefore, the structural investigation of this unusual SH2 domain should increase our understanding of the interaction of this SH2 domain with RNAPII CTD. Recently, three groups reported the crystal structures of two tandem SH2 domains of Saccharomyces cerevisiae, Candida glabrata, and Antonospora locustae Spt6 (22)(23)(24). They found that the tandem SH2 domains directly bound to Ser 2 -phosphorylated RNAPII CTD, and both SH2 domains were essential for Spt6 function in vivo.…”
mentioning
confidence: 99%